Undernutrition and Its Associated Factors Among Human Immunodeficiency Virus Infected Children on Follow Up in Amhara Region Referral Hospitals, Ethiopia, 2020 - Nigatu Dessalegn Msc; Shiferaw Birhanu Msc; Minyichil Birhanu Msc; Amare Kassaw Msc; Kassa Kindie Msc; Amanual Adugna Msc (SAGE Publishing, 2021)
Background. Undernutrition is a global problem and the biggest threat to human life and economic progress. It is the main cause of child morbidity and mortality especially in sub-Saharan Africa including Ethiopia. The severity of the problem is even worse when children are infected with human immunodeficiency virus. However the seriousness of the problem, there were limited studies conducted in the study area. Therefore, this study was conducted to assess the magnitude of undernutrition and its associated factors among HIV-infected children on follow up in Amhara Region Referral Hospitals. Methods. A facility-based cross-sectional study was conducted from February to April 2020. The data were collected through an interviewer-administered questionnaire. The collected data were coded and entered into Epi data 3.1 and exported to SPSS 26.0 for analysis. P -value <.05 was considered as statically significant. Results . The magnitude of undernutrition in this study was 30.3%. Dietary diversity (AOR = 1.73; CI 1.07-2.81), nutritional counseling (AOR = 2.42; CI 1.45-4.04), family size (AOR = 0.50; CI 0.27-0.93), WHO staging (AOR = 1.77; CI 1.08-2.88), and adherence to antiretroviral therapy (AOR = 1.75; CI 1.06-2.87) were predictors of undernutrition. Conclusions . Nearly one-third of the children included in this study had undernutrition. Poor dietary diversity, adherence to ART, nutritional counseling, family size, and WHO staging were factors significantly associated with undernutrition. Early screening and treatment of opportunistic infections, close attention to dietary counseling for caregivers and proper feeding habits will alleviate the problem.